2016
DOI: 10.1186/s12967-016-1037-z
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine reduces MDSCs, tregs and TGFβ-1 while restoring the teff/treg ratio in patients with pancreatic cancer

Abstract: BackgroundCancer immunotherapy can be potentiated by conditioning regimens such as cyclophosphamide, which reduces the level of regulatory T cells (tregs). However, myeloid suppressive cells are still remaining. Accordingly to previous reports, gemcitabine improves immune status of cancer patients. In this study, the role of gemcitabine was further explored to map its immunological target cells and molecules in patients with pancreatic cancer.MethodsPatient blood was investigated by flow cytometry and cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 38 publications
6
143
0
Order By: Relevance
“…Low dose chemotherapy has been shown to be effective in eliminating MDSC populations in tumour-bearing mice; treatments with chemotherapy such as 5-fluorouracil (5FU), paclitaxel, cisplatin, and gemcitabine were found to deplete MDSCs and enhance anti-tumour immune activity [200][201][202][203]. However, a contrasting effect in the use of chemotherapy against MDSC was observed where MDSCs were transiently induced following cyclophosphamide treatment in tumour-bearing mice and patients [204,205].…”
Section: Depleting Mdsc Populationsmentioning
confidence: 99%
“…Low dose chemotherapy has been shown to be effective in eliminating MDSC populations in tumour-bearing mice; treatments with chemotherapy such as 5-fluorouracil (5FU), paclitaxel, cisplatin, and gemcitabine were found to deplete MDSCs and enhance anti-tumour immune activity [200][201][202][203]. However, a contrasting effect in the use of chemotherapy against MDSC was observed where MDSCs were transiently induced following cyclophosphamide treatment in tumour-bearing mice and patients [204,205].…”
Section: Depleting Mdsc Populationsmentioning
confidence: 99%
“…It is also possible that vaccines upregulate multiple immune escape mechanisms, and elucidation of these would be necessary to ensure vaccine efficacy. As chemotherapy transiently depletes suppressive Tregs in PDAC patients (3739), chemotherapy should be considered in addition to administration of an immunomodulatory agent to attempt to overcome the potent immunosuppressive TME.…”
Section: Clinical Challenges In Developing Immunotherapies For Pdacmentioning
confidence: 99%
“…(Table 1). Gemcitabine-based chemotherapy is often used as the chemotherapy backbone in these combination immunotherapy trials because it has been shown to increase tumor antigen availability, and transiently deplete immunosuppressive Tregs and myeloid derived suppressor cells (MDSC) in the PDAC TME (3739,126). Lower numbers of intratumoral Tregs are associated with increased disease free survival after pancreatectomy (30), suggesting that Treg accumulation is an important determinant of survival in patients with PDAC.…”
Section: Vaccine Immunotherapy Strategies For Pdac Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our intraperitoneal‐dissemination and liver‐metastasis PDAC mice models, GEM treatment decreased numbers of myeloid cells and increased CD4+ and CD8+ cells. In other cancer mice model, GEM was proven to be suppressive to myeloid‐lineage cells, especially, myeloid‐derived suppressor cells . Additionally, in BALB/c mice system, GEM depleted B‐lymphocytes; in contrast, tumor‐specific CD4+ and CD8+ cells were augmented .…”
Section: Discussionmentioning
confidence: 99%